The Compact Macronuclear Genome of the Ciliate Halteria grandinella: A Transcriptome-Like Genome with 23,000 Nanochromosomes - Zheng, Weibo (mBio, 2021)
How to achieve protein diversity by genome and transcriptome processing is essential for organismal complexity and adaptation. The present work identifies that the macronuclear genome of Halteria grandinella, a cosmopolitan unicellular eukaryote, is composed almost entirely of gene-sized nanochromosomes with extremely short nongenic regions. This challenges our usual understanding of chromosomal structure and suggests the possibility of novel mechvanisms in transcriptional regulation. Comprehensive analysis of multiple data sets reveals that Halteria transcription dynamics are influenced by: (i) nonuniform nanochromosome copy numbers correlated with gene-expression level; (ii) dynamic alterations at both the DNA and RNA levels, including alternative internal eliminated sequence (IES) deletions during macronucleus formation and large-scale alternative splicing in transcript maturation; and (iii) extremely short 5′ and 3′ untranslated regions (UTRs) and universal TATA box-like motifs in the compact 5′ subtelomeric regions of most chromosomes. This study broadens the view of ciliate biology and the evolution of unicellular eukaryotes, and identifies Halteria as one of the most compact known eukaryotic genomes, indicating that complex cell structure does not require complex gene architecture.